Incorporating Malaysian's population anthropometry data in the design of an ergonomic driver's seat - Md Deros, Baba; Hassan, Nor Hassanil Hanief; Daruis, Dian Darina Indah; Mohd Tamrin, Shamsul Bahri (Elsevier, 2015)
An ergonomically designed driver's seat is crucial in ensuring quality, comfort and safe driving. The increase in road accidents every year is mostly linked to drivers’ fatigue. Therefore, posture comfort is an important aspect in driver's seat design. The aim of this study is to design a driver's seat which is suitable for Malaysians. There are three main objectives in this study; firstly, to investigates the comfort level and safety system of the existing driver's seat, secondly, to identify and determine parameters which may affect comfort and the driver's seat safety system, and lastly, to develop and design an ergonomic driver's seat. Anthropometric data of drivers should be used during the driver's seat design stage. Critical dimensions of the driver's seat and anthropometric data must be taken into consideration in order to optimize the comfort level and safety of the seat. Previous studies showed that the evaluation of driver's seat discomfort should include both objective and subjective evaluations. The seat discomfort will negatively affect the driver's performance. All information pertaining to the driver's seat design was obtained through research on the related subjects. In the data collection phase, the objective evaluation method was used in determining the seat's dimension while subjective evaluation was used to gather information on the drivers’ experience. Anthropometric data from 1405 male and female subjects were collected and stored in a database. Meanwhile, subjective evaluation on driver's seat discomfort was conducted on 100 male and female respondents. The SPSS software was used to analyse the data. Every parameter that affects the safety and comfort of the driver's seat were then used to design a new driver's seat. The parameters that were taken into account are backrest height, cushion width, cushion length and adjustability. These parameters were then matched with the Malaysian drivers’ anthropometric data. Finally, the dimensions of the new driver's seat were determined: 520 mm cushion width; 380 mm cushion length, 480 mm backrest width, 407.5 mm backrest height and 180 mm adjustability.